Situational interest, computer self-efficacy and self-regulation: Their impact on student engagement in distance education - Sun, Jerry Chih-Yuan; Rueda, Robert (British journal of educational technology, 2012)
This study investigates possible relationships among motivational and learning variables (interest, self‐efficacy and self‐regulation) and three types of student engagement (behavioural engagement, emotional engagement and cognitive engagement) in a distance education setting. Participants were 203 students enrolled in online classes in the fall semester of 2008 in the Schools of Gerontology and Engineering at a large research university in the south‐western USA, who completed an online survey assessing their levels of situational interest, computer self‐efficacy, self‐regulation and engagement in distance education. Situational interest and self‐regulation were found to be significantly correlated with three types of engagement (behavioural, emotional and cognitive), while computer self‐efficacy did not appear to be associated with any of those engagement variables. Results suggested that online activities and tools such as multimedia and discussion boards may increase emotional engagement in online learning, although they do not necessarily increase behavioural or cognitive engagement, that educators should identify students who are taking online courses for the first time and provide necessary technical help to increase their emotional engagement, and that it is important for educators to offer students strategies for increasing their self‐regulation in distance education environments.